Avaliação do Programa Conviver na Perspectiva do Idoso Participante - Ribeiro, Mary Anne Libório de Patrício (2011)
This research aimed at evaluating the actions of the Program “Living Together” the elderly as a strategy to put into practice the National Policy of Social Welfare, in Fortaleza. Its purpose was also aim to calculate the number of elderly patients from 2003 to 2009 and to analyze the level of satisfaction in their living; it also aimed at estimating if there had been any changes in the lives of the participants since they had joined the Program. Another objective of this research is to suggest improvements and eventual enhancements in the methods currently used, based upon the results which had been collected during the above mentioned period. The study was conducted in eight community centers of the Department of Labor and Social Development of the State of Ceará, located in Fortaleza, which run this program through Support Groups. The research consisted of a quantitative study associated with the use of documentary and secondary data. Data collection took place from 01/06/2010 to 31/07/2010. The sample comprised 262 seniors out of 820 elderly who had participated in the groups for no less than six months. We used a questionnaire which was applied to the groups of elderly with the purpose of investigating their socioeconomic profiles and their level of satisfaction regarding the activities which had been put into practice in the groups from 2003 to 2009. The demographic and socioeconomic data were grouped according to absolute and relative frequency and arranged in frames and tables. Data analysis was carried out based upon the key assumptions Program “Living Together” and the National Policy for Social Assistance according to the most up-to-date literature related to this subject. The results of our research were, in general, the following: Most of the subjects in our study are female, widowed, single or divorced. They all had low educational level, and from the hinterland of the state of Ceará; most of them reside with their sons, daughters or other relatives; they are retired people or receive the Benefit of “Continuous Support”. A certain lack of planning among community centers and the Groups was found. It was observed that the Groups develop without a major connection with the other programs and projects that could benefit the elderly. However, in spite of a few weak points detected, the subjects evaluated positively the “Living Together” Program, indicating substantial changes in their life routine, a sound interaction with other groups and with their family members as well as increased provision and improved self-esteem. It is legitimate to conclude that the program must go through a process of redirection of its goals and that the Program should never fall into the hands of the municipalities, something which would make future assessments more difficult. Likewise, it is felt that the Program should undergo a process of diversification of activities by focusing on the professional training of participants and the prevention of dementia, greater coordination among the Coexistence groups and other programs, projects and services of the Community Centers, professional qualification of personnel, ensuring a regular state budget enough to cover the existing expenses that the activities involve and to extending them, expanding coverage, planning of joint actions with other public policies involving Aged care; elderly participation in the planning of interventions, based on their needs, wants and desires, recognizing their autonomy and ability to propose improvements in their lives.